British Collective Bargaining : The Challenges of the 1970’s - Banks, Robert (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1971)
In the 1960's Britain’s traditional industry-wide collective bargaining system was modified significantly by the growth of local bargaining, the introduction of an incomes policy and government recommendations for the general reform of industrial relations. Other important innovations were long term agreements, status agreements and productivity bargaining. The Conservative Governments new Industrial Relations Act will have a significant impact on the industrial relations system, particularly with regard to union recognition, internal unions affairs and the protection of the rights of individual employees. However, the Acts restrictions on the right to strike are likely to have only a minimal impact on established bargaining relationships. As Great Britain enters the 1970's the industrial relations system's main challenge is for unions and management to voluntarily respond to the problems which continue to be posed by the uncoordinated growth of plant bargaining.